Non‐masticatory dental wear patterns in individuals exhumed from the Middle Bronze Age rock‐cut tombs of Torre Velha 3 (Serpa, Portugal). (15th November 2019) - Fidalgo, Daniel; Silva, Ana Maria; Porfírio, Eduardo
Abstract: Dental examination of 21 individuals (11 females, nine males and one undetermined sex) exhumed from the rock‐cut tombs of Torre Velha 3 (Serpa, Portugal), dating from the 2 nd millennium BC, revealed dental wear features and oral lesions that can be linked to non‐masticatory activities and/or dietary habits. A total of 471 teeth were macroscopically analyzed. One young‐adult female and a middle‐age adult of unknown sex display lingual surface attrition of the maxillary anterior teeth (LSAMAT). A middle‐age adult female has LSAMAT, anterior occlusal surface groove (AOSG) and chipping. Two other middle‐age adult females have oblique wear planes (OWP), one of them also with chipping. Overall variation and low frequencies of the observed alterations suggest that multiple activities and/or dietary habits could have caused these wear patterns. The hypothesis that atypical wear patterns are sex biased was tested using Fischer's exact test, and results were not statistically significant (p‐value = 0.09). Thus, it is possible to infer that these individuals had possible dietary or cultural idiosyncratic behaviors, besides repetitive non‐masticatory task related‐activities.